A Perspective from Los Angeles of COVID‐19 effect and impact on cardiac surgery. Issue 5 (5th October 2020) - Worthington, Tiffany; Khoynezhad, Ali
Abstract: Coronavirus 2019 (COVID‐19) captured worldwide attention as the virus spread from initial detection as a pneumonia of unknown cause in Wuhan, China in December 2019 to the declaration of a pandemic by the WHO only 3 months later. This paper describes the impact of COVID‐19 on cardiac surgery services in the greater Los Angeles area. Discussion includes public health response to the pandemic, how local hospitals reacted to the expected surge in patients with COVID, the establishment of telemedicine services, and the projected future impact on California healthcare as a result of the COVID‐19 pandemic.